Chile: Demand and Supply Projections for Agricultural Products, 1965-1980 - Santiago de Chile; United States (Jerusalem : Published for the U.S. Dept. of Agriculture, Economic Research Service, by the Publication Services Division of the Israel Program for Scientific Translations, 1969)
The purpose of this study is to present demand and supply projections for thirty-eight Chilean agricultural products for the years 1970, 1975, and 1980, 1965 being considered as the base year.
ne 7/03/2018
Loan
Keywords: Farm produce; Food consumption; Food supply